Analysis of the Effect of Regional Original Income and Balanced Funds on Regional Financial Independence in North Maluku Province Local Governments - Hostaf Prio Da Gama; Rusman Soleman; Hartaty Hadady (Jurnal Economic Resource, 2022)
This study aims to determine and analyze the effect of regional original income and balancing funds on regional financial independence in regional governments in North Maluku Province. The sample in this study used a purposive sampling method. Based on the sample selection with the criteria, 11 local governments in North Maluku Province or 55 observation units were selected within a period of 5 years. The analytical method used in this research is panel data analysis. The results of the study show that regional original income has a significant positive effect on regional financial independence and the balancing fund has a significant negative effect on regional financial independence in each local government in North Maluku Province.